Polyphenols and Polysaccharides from Morus alba L. Fruit Attenuate High-Fat Diet-Induced Metabolic Syndrome Modifying the Gut Microbiota and Metabolite Profile - Meixia Wan; Qing Li; Qianya Lei; Dan Zhou; Shu Wang (Foods, 2022)
Morus alba L. fruit, a medicinal and edible fruit in East Asia, showed potential health-promoting effects against metabolic syndrome (MetS). However, both the protective effects and mechanisms of different fractions extracted from Morus alba L. fruit against MetS remain unclear. Additionally, the gut microbiota and its metabolites are regarded as key factors in the development of MetS. This study aimed to investigate the potential role of polyphenols and polysaccharides derived from Morus alba L. fruit against MetS in high-fat diet (HFD)-fed mice, individually and in combination, focusing on remodeling effects on gut microbiota and metabolite profiles. In the study, polyphenols and polysaccharides derived from Morus alba L. fruit improved the traditional pharmacodynamic parameters of MetS, including reductions in body weight (BW) and fat accumulation, improvement in insulin resistance, regulation of dyslipidemia, prevention of pathological changes in liver, kidney and proximal colon tissue, and suppressive actions against oxidative stress. In particular, the group treated with polyphenols and polysaccharides in combination showed better efficacy. The relative abundance of beneficial bacterial genera Muribaculum and Lachnospiraceae_NK4A136_group were increased to various degrees, while opportunistic pathogens such as Prevotella_2, Bacteroides, Faecalibacterium and Fusobacterium were markedly decreased after treatments. Moreover, fecal metabolite profiles revealed 23 differential metabolites related to treatments with polyphenols and polysaccharides derived from Morus alba L. fruit, individually and in combination. Altogether, these results demonstrated that polyphenols and polysaccharides derived from Morus alba L. fruit attenuated MetS in HFD-fed mice, and improved the gut microbiota composition and fecal metabolite profiles.